La citazione meccanica. Una rassegna sul fenomeno dell’ecolalia - Greta Mazzaggio (Parole Rubate, 2019)
For some people quoting is the only way to communicate. In some pathologies, the difficulty in creating declarative clauses can be partially overcome through alternative strategies such as the mechanical and stereotyped repetition of words or sentences spoken by another person. In the past, this phenomenon – known as echolalia – was considered as a deficiency to be corrected. This article explores the debate over the communicative value of echolalia, drawing upon some studies which have demonstrated how imitation can play an essential role in the communication of children with language disorders.